2020
DOI: 10.1177/0267659120978647
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of postoperative atrial fibrillation persisting beyond hospital discharge after coronary artery bypass grafting

Abstract: Objective: Minimal invasive extracorporeal circuits (MiECC) have been associated with a significant reduction in the incidence of postoperative atrial fibrillation (AF). Nevertheless, AF remains one of the most common complications following elective primary coronary artery bypass grafting (CABG). The aim of this study was to identify the predictors of AF persisting beyond the hospital stay in elective primary CABG patients. Methods: We conducted a retrospective analysis for the predictors of AF that persisted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There is increasingly solid evidence coming from large-scale studies 59 and meta-analyses demonstrating a reduced incidence of postoperative AF with MiECC use. 47,49,51 However, one recent single-centre randomized study of 240 patients reported no difference in AF between both arms (MiECC and cCPB) after coronary surgery.…”
Section: Methodsmentioning
confidence: 99%
“…There is increasingly solid evidence coming from large-scale studies 59 and meta-analyses demonstrating a reduced incidence of postoperative AF with MiECC use. 47,49,51 However, one recent single-centre randomized study of 240 patients reported no difference in AF between both arms (MiECC and cCPB) after coronary surgery.…”
Section: Methodsmentioning
confidence: 99%
“…Factors such as atrial dilation, ischemia, inflammation, atrial remodeling, trauma, autonomic imbalance and post-extracorporeal circulation could all contribute to AF after a CABG procedure [ 131 ]. At the same time, minimal invasive extracorporeal circuits have been associated with a significant reduction in the incidence of POAF [ 132 ]. POAF was associated with a lower survival rate compared to patients remaining in sinus rhythm at the 10-year follow-up (65.5% vs. 75.3%) [ 133 ].…”
Section: Mirna Expression Changes In Patients With Atrial Fibrillation Undergoing Cabg Proceduresmentioning
confidence: 99%